Exploring the dimensions of responsible research systems and cultures: a scoping review - Sarahanne M. Field; Jackie Thompson; Sarah de Rijcke; Bart Penders; Marcus R. Munafò (Royal Society Open Science, 2024)
The responsible conduct of research is foundational to the production of valid and trustworthy research. Despite this, our grasp of what dimensions responsible conduct of research (RCR) might contain—and how it differs across disciplines (i.e. how it is conceptualized and operationalized)—is tenuous. Moreover, many initiatives related to developing and maintaining RCR are developed within disciplinary and institutional silos which naturally limits the benefits that RCR practice can have. To this end, we are working to develop a better understanding of how RCR is conceived and realized, both across disciplines and across institutions in Europe. The first step in doing this is to scope existing knowledge on the topic, of which this scoping review is a part. We searched several electronic databases for relevant published and grey literature. An initial sample of 715 articles was identified, with 75 articles included in the final sample for qualitative analysis. We find several dimensions of RCR that are underemphasized or are excluded from the well-established World Conferences on Research Integrity (WCRI) Singapore Statement on Research Integrity and explore facets of these dimensions that find special relevance in a range of research disciplines.